Peripheral retinal leakage in POEMS syndrome - Carey, Andrew Rising (Int J Retina Vitreous, 2021)
BACKGROUND: POEMS (polyneuropathy, organomegaly, endocrinopathy, myeloma protein, skin changes) syndrome is a rare blood disorder with multi-system involvement. The cause is unknown. It is marked by elevated plasma cells, platelets, & VEGF (vascular endothelial growth factor) levels. 52% of patients develop optic disc edema which may be vision threatening but the exact etiology of optic disc edema is uncertain. We report a rare finding of peripheral retinal leakage in POEMS syndrome. CASE PRESENTATION: A 60 year-old female with POEMS syndrome presented with bilateral blurred vision. Fundi showed grade 3 disc edema OU. Lumbar puncture showed normal opening pressure. CSF analysis showed elevated proteins with no cells. MRI brain and MR Venogram head were unremarkable. Wide field fluorescein angiography demonstrated multifocal tiny vascular leakage and significant anterior temporal leakage. CONCLUSION: The authors hypothesize the disc edema in POEMS syndrome may be caused by increased vascular permeability at the optic disc secondary to increased VEGF (vascular endothelial growth factor) levels. Though disc leakage is a well-documented finding in fundus fluorescein imaging, peripheral retinal leakage in POEMS syndrome is not reported.